The Current Role of Accounting Information Systems - Tóth, Zsuzsanna (Theory, Methodology, Practice – Review of Business and Management, 2012)
The primary purpose of this paper is to present the actual role of accounting information systems. After the description of the theoretical background I state the main characteristics of modern accounting systems, and explain how these software packages can efficiently help not only the work of the accountant, but also of the management